Comic book women : characters, creators, and culture in the Golden Age - Brunet, Peyton; Davis, Blair (World comics and graphic nonfiction series., 2022)
"The Golden Age of Comics (roughly the late 1930s through the 1950s) saw the birth and rapid growth of the industry, but unfortunately and unsurprisingly the role of women was often problematic during this period. Few women creators worked in comics, and those that did frequently worked anonymously or under pseudonyms and were subject to workplace harassment and discrimination. Similarly, female characters were often poorly presented and framed in a sexualized fashion. Although some elements of this history have been told piecemeal there hasn't yet been a comprehensive look at women in comics during this period. Brunet and Davis examine female creators and characters across a broad range of genres to create a historical narrative of representation and culture that goes beyond previous scholarship"--